Diet Pada Penderita Hipertensi Di Komplek Singgalang Lubuk Buaya Kota Padang - Hasmita Hasmita; Miswarti Miswarti (BADAN PENERBIT STIEPARI PRESS, 2022)
Hypertension is a condition when blood pressure is at 130/80 mmHg or more. The World Health Organization (WHO) estimates 30% of the world's population. Based on Basic Health Research (Riskesdas 2018) the prevalence of hypertension in Indonesia is 34.1%. This has increased compared to the prevalence of hypertension in the 2013 Riskesdas of 25.8%. Hypertension is divided into two types, namely primary and secondary hypertension. Primary hypertension tends to develop gradually over years and eventually gets worse if not treated. If hypertension occurs for years without treatment or efforts to control it, the sufferer can experience various complications of hypertension. which is dangerous. Management of hypertension can be done pharmacologically, namely by using anti-hypertension drugs (Ode, 2012). Another way that is best for controlling hypertension is by controlling diet. The Winshiel Survey which was carried out for 2 days at the Singgalang Lubuk Buaya Housing Complex, Padang City, found that the most common disease was hypertension. This is due to people's habits of consuming high-fat, fried foods. offal and have unhealthy lifestyles such as smoking habits. Based on the problems above, it is necessary to have community service to be able to cooperate between various parties in preventing hypertension. The aim of this community service is so that hypertension sufferers can understand diet and prevent hypertension. The service was carried out for hypertension sufferers in September 2022. The results of the service showed that 87 of participants could explain the meaning of hypertension. 91% of participants could explain hypertension diet. 87% could explain the management of hypertension diet, 91% could explain the principles of diet for hypertension sufferers. 91% of participants could explain foods that should be avoided by hypertension sufferers